2011
DOI: 10.1016/j.febslet.2011.01.032
|View full text |Cite
|
Sign up to set email alerts
|

AP-site cleavage activity of tyrosyl-DNA phosphodiesterase 1

Abstract: Keywords:DNA repair AP site Tyrosyl-DNA phosphodiesterase 1 enzyme property a b s t r a c t APE-independent base excision repair (BER) pathway plays an important role in the regulation of DNA repair mechanisms. In this study it has been found that recently discovered tyrosyl-DNA phosphodiesterase 1 (Tdp1) catalyzes the AP site cleavage reaction to generate breaks with the 3 0 -and 5 0 -phosphate termini. The removal of the 3 0 -phosphate is performed by polynucleotide kinase phosphatase (PNKP). Tdp1 is known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 15 publications
3
63
0
Order By: Relevance
“…The importance of TDP1 outside Top1cc repair was first shown for 3′-phosphoglycolate ends and 3′-deoxyribose phosphate ends (Fig. 3E), which are common products of oxidative DNA damage as well as from radiomimetic drugs such as bleomycin [45,52,6165]. Accordingly, TDP1 knockout cells are deficient in repairing oxidative DNA damage both in mitochondria and the nucleus [43,66,67].…”
Section: Tyrosyl-dna Phosphodiesterase 1 (Tdp1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of TDP1 outside Top1cc repair was first shown for 3′-phosphoglycolate ends and 3′-deoxyribose phosphate ends (Fig. 3E), which are common products of oxidative DNA damage as well as from radiomimetic drugs such as bleomycin [45,52,6165]. Accordingly, TDP1 knockout cells are deficient in repairing oxidative DNA damage both in mitochondria and the nucleus [43,66,67].…”
Section: Tyrosyl-dna Phosphodiesterase 1 (Tdp1)mentioning
confidence: 99%
“…TDP1 also efficiently hydrolyzes 3′-deoxyribose lesions resulting from base alkylation after AP lyase processing [45,65]. This activity is particularly relevant for the repair of DNA lesions induced by monofunctional alkylating agents including methylmethanesulfonate and temozolomide, and ionizing radiations [45,53].…”
Section: Tyrosyl-dna Phosphodiesterase 1 (Tdp1)mentioning
confidence: 99%
“…CPTs, which include the Food and Drug Administration-approved analogs topotecan and irinotecan, reversibly stabilize the covalent Top1-DNA complex to induce S phase-specific lethal DNA lesions (2)(3)(4)(5)(6). More recently, Tdp1 has been shown to process a wide range of other DNA adducts, including 3Ј-modified nucleotides, such as phosphoglycolates and chain-terminating nucleotides, and a 3Ј-phosphohistidyl intermediate formed during Tdp1 catalysis (7)(8)(9)(10)(11)(12)(13).…”
Section: Tyrosyl-dna Phosphodiesterase I (Tdp1)mentioning
confidence: 99%
“…Tdp1 can also process protruding 3'-phosphoglycolate termini on DSBs (Inamdar et al, 2002) and cleave phosphoamide bonds (Interthal et al, 2001). The enzyme participates in non-homologous end joining (NHEJ) (Bahmed et al, 2010) and base excision repair (BER) (Lebedeva et al, 2011). The expanding literature on the Tdp1 function has revealed that animal systems possess either DNA repair pathways able to remove the stabilized topo I-DNA covalent complexes in parallel with the Tdp1-mediated repair pathway or alternative DNA repair pathways which are activated in the Tdp1-depleted cells.…”
Section: Introductionmentioning
confidence: 99%